Plastination technology for anatomical studies in Nigeria: Opinion of teachers at medical institutions - Onyemaechi O. Azu; Aniekan I. Peter; Aquaisua N. Aquaisua; Gabriel J.Ekandem (AOSIS, 2013)
Dr. Gunther von Hagens developed plastination as a technique of tissue preservation in 1977. He used a delicate method of forced impregnation with curable polymers like silicone, epoxy or polyester resins for preservation of anatomical specimens. With plastination, every part of a biological tissue is treated, preserving it for educational purposes. Hence, there are vast applications in the medical field. We set out to survey the knowledge and opinion of lecturers of anatomy about plastinated specimen use in medical schools through the administration of questionnaires to respondents who participated at the Society of Experimental and Clinical Anatomists of Nigeria (SECAN) conference in 2011. It was found that 50.0%and 23.75%of respondents respectively, had their masters and doctorate degrees in Anatomy. Less than 8.0% utilised plastination as a tool for teaching as against 40%(plastic models), 36.25%(cadavers) and 15.0%(pathology pots). Conventional methods such as fixation by immersion (15.0%) and embalming (52.5%) with formaldehyde were commonly used for long term preservation of tissues in their various institutions. These methods were found to be less costly (25.0%), easy to use (56.25%) and the only method (12.25%) available, even though they posed some health hazards (96.0%). Whilst only 6.25%of the respondents did not know anything about plastination, 93.75%were aware of it. The advocacy for preservation of tissues by plastination has been gradual in developed countries. We recommend the use of plastinates in medical schools in Nigeria.